Bilateral Diffuse and Cluster Pigment Epithelial Detachment Associated with Diffuse Proliferative Glomerulonephritis - Heshmatollah Ghanbari; Alireza Dehghani; Mohsen Pourazizi (Case Reports in Ophthalmological Medicine)
Retinal pigment epithelium detachment (PED) is an area of retinal pigment epithelium (RPE) elevation with minimal or no sensory retinal detachment resulting from the accumulation of sub-RPE fluid. There are many etiological factors that lead to the development of PED. PED may be observed as an isolated finding or in association with ocular and systemic conditions. In this case we report a 23-year-old male with bilateral cluster PED associated with diffuse proliferative glomerulonephritis (DPGN). The importance of current report is that development of PED and DPGN is more than a simple incidental event. Patients with DPGN should have regular fundus examinations, and follow-up should be conducted by an ophthalmologist who is aware of the possible presence of these diseases.